Intelligent Human Computer Interaction 14th International Conference, IHCI 2022, Tashkent, Uzbekistan, October 20-22, 2022, Revised Selected Papers - Zaynidinov, Hakimjon; Singh, Madhusudan; Tiwary, Uma Shanker; Singh, Dhananjay (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 14th International Conference on Intelligent Human Computer Interaction, IHCI 2022, held in Tashkent, Uzbekistan, during October 20-22, 2022. The 47 full papers and 13 short papers included in this book were carefully reviewed and selected from 148 submissions. They were organized in topical sections as follows: Bio-inspired Computing; Cognitive computing; Human Centered AI; Intelligent Technology for Post-Covid and Web Frameworks.
Deep fake video detection using the frequency characteristic of remote photoplethysmography -- A Multi-Layered Deep Learning Approach for Human Stress Detection -- Digital Processing Algorithms Of Biomedical Signals Using Cubic Base Splines -- Algorithms for selecting and comparing features of digital image vectors based on the analysis of local extrema -- Calculation Of Spectral Coefficients Of Signals On The Basis Of Haar By The Method Of Machine Learning -- Optimization of fractal structure pattern colors in carpet design using genetic algorithm -- Algorithm For Digital Processing Of Seismic Signals In Distributed Systems -- Methods for creating a morphological analyzer -- Uzbek Speech Synthesis Using Deep Learning Algorithms -- Speech Recognition Technologies Based on Artificial Intelligence Algorithms -- Multimodal Human Computer Interaction using Hand Gestures and Speech -- Emotion Recognition in VAD space during Emotional Events using CNN-GRU hybrid model on EEG Signals -- Multiclass Classification of online reviews using NLP & Machine Learning for Non-English Language -- A Higher Performing DARTS Model for CIFAR-10 -- Automatic speech recognition on the neutral network based on attention mechanism -- Equal Temperament and Just intonation Feature based Emotion Predictions in Carnatic Music -- Emotion classification through facial expressions using SVM and Convolutional Neural Classifier -- On the Evaluation of Stylised Lyrics using Deep Generative Models: A Preliminary Study -- GWD: Graded Word Drop Model for When Type Questions for Hindi QA -- Masked Face Recognition Model with Explainable AI -- UX design workshop for building relationships between humans and intelligent objects using 'T+e=B' toolkit -- A Longitudinal Study of the Emotional Content in Indian Political Speeches -- Building A Local Classifier For Component-Based Face Recognition -- Dominance Submissiveness Predisposition Scale (DSPS) : Development and Validation -- Design of a Mixed Reality-based Immersive Virtual Environment System for Social Interaction and Behavioral Studies -- Privacy-preserving Digital Intervention for Mental Health using Federated Learning -- How can humans and robots live together?: The 5 types of human-robot relationship -- Effectiveness Of Deep Learning Based Filtering Algorithm In Separation Of Human Objects From Images -- Building the Groundwork for a Natural Search, to Make Accurate and Trustworthy Filtered Searches: The Case of a New Educational Platform with a Global Heat Map to Geolocate Innovations in Renewable Energy -- Implementation of Virtual Sea Environment with 3D Whale Animation -- A Constant-Factor Approximation Algorithm for Online Coverage Path Planning with Energy Constraint -- Real-time Image based Plant phenotyping using Tiny-YOLOv4 -- Influence Of Packet Switching And Routing Methods On The Reliability Of The Data Transmission Network And The Application Of Artificial Neural Networks -- Do Users' Values Influence Trust in Automation? -- Automation of Calibration Procedure for Milk Non Automatic Weighing Instrument(NAWI) Process -- Low-cost Entry-level Educational Drone with Associated K-12 Education Strategy -- Creating a Modular and Decentralized Smart Mailbox System Using LoRaWan Networks -- A converting model 3D gaze direction to 2D gaze position -- Application of fiber optic sensors in aircraft fuel management system -- Intelligent multi-tariff payment collection system for in-ter-municipal buses in the Department of Atlántico - Colombia -- Agent-based modelling and simulation of public transport to identify effects of network changes on passenger flows -- Exploiting Security and Privacy Vulnerability in Human-IoT Interaction through the Virtual Assistant Technology in Amazon Alexa -- User Experience in Virtual Reality using Threshold Space in between Different Physical Laws -- Monitoring Pollination by Honeybee using Computer Vision -- Modeling the problem of integral geometry on the family of broken lines based on Tikhonov regularization -- A Framework for Privacy-Preserved Collaborative Learning in Smart Factory Environment -- Co-creating Computer Supported Collective Intelligence in Citizen Science Hubs -- Gaze Detection using Encoded Retinomorphic Events -- Extremely Lightweight Skin Segmentation Networks to Improve Remote Photoplethysmography Measurement -- Privacy-Friendly Phishing Attack Detection using Personalized Federated Learning -- CovidMis20: COVID-19 Misinformation Detection System on Twitter Tweets using Deep Learning Models -- Development of School Library Network Based on Cloud Technologies in Uzbekistan -- Parallel Resource Defined Fitness Sharing -- EEG-based Key Generation Cryptosystem for Strengthening Security of Blockchain Transactions -- Improving Gaze Estimation Performance using Ensemble Loss Function -- Non-Overlayed Guidance in Augmented Reality: User Study in radio-pharmacy -- Development Of A Novel Method For Image Resizing Using Artificial Neural Network -- From Angular to Vue: A Cross-Language Comparative Survey of Web Frameworks.
Keywords: User interfaces (Computer systems).; Human-computer interaction; Artificial intelligence; Computer systems; Signal processing; Information technology -- Management; User Interfaces and Human Computer Interaction; Artificial Intelligence; Computer System Implementation; Signal, Speech and Image Processing .; Computer Application in Administrative Data Processing